A direct comparison between in-situ transmission electron microscopy observations and Dislocation Dynamics simulations of interaction between dislocation and irradiation induced loop in a zirconium alloy. (1st July 2016) - Drouet, J.; Dupuy, L.; Onimus, F.; Mompiou, F.
Abstract: Dislocation Dynamics simulations of a dislocation-loop interaction are compared to experimental observations performed during an in-situ straining experiment in a Transmission Electron Microscope at 500 °C on a zirconium alloy, referred to as recrystallized Zircaloy-4, irradiated with Zr ions. The DD simulations, performed in the same geometrical, stress and dislocation mobility conditions, exhibit an excellent agreement with the observed interaction. It is shown that the interaction leads to the formation of an helicoidal turn expanding along the dislocation before being blocked below the sample surface. This approach opens the way to massive Dislocation Dynamics simulations with realistic input data. Graphical abstract: